POSTOPERATIVE PAIN AFTER VENTRAL HERNIA REPAIR: A PROSPECTIVE COMPARISON OF OPEN VERSUS LAPAROSCOPIC WITH INTRAPERITONEAL ONLAY MESH (IPOM) TECHNIQUE - Kadri, Edzevit; Lazova, Evgenija; Jota, Gjorgji; Nanceva, Jasmina; Panik, Katarina (Journal of Morphological Sciences, 2021)
Laparoscopic ventral hernioplasty has many advantages over the open access hernioplasty, but patients suffer severe pain in the first few days.Objectives of this study was comparison of early postoperative pain in Open and Laparascopic approach in IPOM hernioplasty and whether there was statistically significant difference in the intensity of postoperative pain during resting and activity.63 patients who met the inclusion criteria were included in a randomized, prospective, comparative study and were operated with the IPOM technique. They were divided into two groups: open and laparascopic access (32 and 31 patient, consequently). In both groups, postoperative pain was compared at eight time intervals during rest and activity, quantified using VAS. The statistical analysis was done in the statistical programme SPSS version 23.0.Patients undergoing laparoscopic hernioplasty had significantly higher pain intensities on the day of the intervention, the first and second day after the intervention (p<0.0001). On the third and seventh postoperative days, as well as one and six months after the intervention, there was no significant difference in pain intensity between the two methods during rest and activity.Patients after laparoscopic ventral hernioplasty suffer from severe pain in the early postoperative period and it is the biggest challenge and problem after these operations. This originates from transfascial sutures for mesh fixation in both groups and additionally multiple lesions of the parietal peritoneum in the laparoscopic method due to the numerous mesh fixations with tackers. Keywords: Laparoscopic IPOM, open IPOM, postoperative pain https://doi.org/10.55302/JMS2141095k